2019
DOI: 10.21203/rs.2.11843/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacterial profile, antibiotic susceptibility pattern and associated risk factors of urinary tract infection among clinically suspected children attending at Felege-Hiwot Comprehensive and Specialized Hospital, Northwest Ethiopia. A prospective study

Abstract: Background Urinary tract infection is one of the most common bacterial infections in children. Understanding the characteristics of uropathogens and their antimicrobial susceptibility pattern in a particular setting can provide evidence for appropriate management of cases. The aim of this study was to assess the bacterial profile of urinary tract infection, their antimicrobial susceptibility pattern and associated factors among clinically suspected children attending at Felege-Hiwot Comprehensive Specialized … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 21 publications
7
4
1
Order By: Relevance
“…We have found that Gram-negative bacterial isolates exhibited high rates of resistance towards amoxicillin-clavulanate (89.5%), ampicillin (84.6%), tetracycline (73.7%) and co-trimoxazole (68.4%). This is in agreement with the findings of previous studies conducted in Bahir Dar, Ethiopia [ 22 , 31 ], Kenya [ 36 ] and Nigeria [ 37 ]. Our results imply that these antibiotics have only the least efficacy and hence cannot be used in an empirical therapy for the management of UTI in children in the study area.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We have found that Gram-negative bacterial isolates exhibited high rates of resistance towards amoxicillin-clavulanate (89.5%), ampicillin (84.6%), tetracycline (73.7%) and co-trimoxazole (68.4%). This is in agreement with the findings of previous studies conducted in Bahir Dar, Ethiopia [ 22 , 31 ], Kenya [ 36 ] and Nigeria [ 37 ]. Our results imply that these antibiotics have only the least efficacy and hence cannot be used in an empirical therapy for the management of UTI in children in the study area.…”
Section: Discussionsupporting
confidence: 93%
“…Results of our study also revealed that isolates of E. coli were highly resistant to ampicillin, amoxicillin-clavulanate and tetracycline 77.8% each (7/9), and co-trimoxazole 66.7% (6/9), which are comparable to the outcome of studies conducted in Bahir Dar, Ethiopia [ 22 ], and Nepal [ 33 ]. In addition, it is to be noted that 77.8% (7/9), 66.7% (6/9) and 55.% (5/9) of E. coli were resistant to ceftazidime, cefuroxime and ceftriaxone, respectively, which are comparable to the results of studies conducted in India [ 38 ] and Bangladesh [ 39 ].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In Ethiopia, few studies were conducted to determine urinary tract infections among pediatric patients: the study at Hawassa referral hospital, Yekatit 12 hospital, Felege-Hiwot specialized, and Gondar University hospitals revealed 27.5%, 19 15.9%, 20 16.7%, 21 and 26.45%, 22 respectively. The lack of urine culture in health facilities with different levels in developing countries including Ethiopia remained impractical as they are resource-intensive.…”
Section: Introductionmentioning
confidence: 99%